Answer:
Step-by-step explanation:
The sum of angle measures is ...
(7x +13)° +(83 -2x)° = 141°
5x +96 = 141 . . . . . collect terms, divide by °
5x = 45 . . . . . . . . . subtract 96
x = 9 . . . . . . . . . . . divide by 5
7x +13 = 7·9 +13 = 76 . . . . . find m∠J
m∠J = 76°
m∠K = 141° -76°
m∠K = 65°
Answer:
Step-by-step explanation:
#8
step #1: <em><u>add $24.94 with $3.82</u></em>
24.94 + 3.82 = 28.76
Step #2: <u><em>subtract </em></u>
$50 - 28.76 = <u>$21.24</u>
Answer: it is the 4th graph
Step-by-step explanation:
(-3,25)(0,20)(3,16)(6,12.8)
Answer:
Step-by-step explanation:
Social Security Administration
Answer:

Step-by-step explanation:
We are going to apply algebra to solve for the exponential growth
we know that the expression for the exponential formula is

where
a = the amount before measuring growth or decay
= 10,000
r = growth or decay rate = 23%= 0.23
x = number of time intervals that have passed
since this problem is on the growth we are going to replace "b" with (1+r), likewise for decay (1-r)
hence the formula becomes


The expression that will give the population value is
